E-fulfilling the e-supply chain of digital print. (14th January 2008) - Papagiannidis, Savvas; Bourlakis, Michael; Li, Feng
This paper employs a qualitative case study methodology aiming to shed light on the integration process between the supply chain and the information technology operations of a business network in the UK digital print sector. That integration process, combined with the simultaneous and parallel transformation of the supply chain management operations in order to distribute and print material online, via numerous partners and distributors, results in the emergence of a fourth party digital print logistics network. The unique characteristics of the network are related to the fast response to on-print customer demand and to the ability to print material in numerous locations; hence, it is gradually becoming a demand-chain digital print logistics network. It also illustrates a new business model and a new way of working, enabled by the internet and related technologies, that were not financially viable in the past.